ダイ 31 ジ ナンキョク チイキ カンソク タイ ショウワ キチ エットウ 1990 ホウコク - 内藤, 靖彦; ナイトウ, ヤスヒコ; Naito, Yasuhiko (1992)
P(論文) 第31次昭和基地越冬隊30名は1990年2月1日より翌1991年1月31日まで昭和基地に滞在して, 基地の維持・管理をしつつ種々の観測, 設営の活動を行った。定常観測として気象, 電離層, 地球物理の観測をほぼ例年どおり実施した。例年と異なる点は, 例年より多いオゾンゾンデ観測とSTS高精度地震計の本格的運用であった。研究観測は, 気水圏系による海氷現場観測を主体とした「海氷-大気相互作用の研究」の種々の観測, 宙空系, 気水圏系によるEXOS-D, MOS-1衛星などの衛星観測, 生物・医学系によるペンギン類の採食生態の種々の観測が中心課題であった。これら以外にも多くの観測を年間を通して実施し予定どおりの成果を得た。設営面でも多くの活動を行った。基地の管理・維持については, 隊の安全管理の面からも施設, 設備の点検を年間を通して実施した。特記すべき点は, 冬期に発電機の2機並列運転を本格的に行ったこと, 廃棄物処理を本格的に実施したことである。廃棄物処理については, 焼却炉の運用, 廃棄物の持ち帰りなどを行った。野外活動は海氷旅行を中心に実施したが, 年間を通して安定した海氷に恵まれ予期以上の成果を得た。航空機の運用も海氷の安定により年間を通して行うことができた。内陸旅行は夏と冬明けにみずほ, 及び秋にH-180までの旅行を実施した。 Japanese Antarctic Research Expedition (JARE) dispatched two wintering parties to Syowa and Asuka Stations in Antarctica. The report describes the activities of the JARE-31 wintering party at Syowa Station. A total of 30 members, including 15 scientists and 15 logistics, had stayed at the station from 1 February 1990 to 31 Jaunary 1991. The major tasks assigned to the wintering party by the JARE headquarters were to conduct more than 60 items of the observation including launching of the ozone sonde and total ozone observation as a routine meteorological observation, STS earthquake observation, field experiments of ACR program with major focuss on the interaction between sea ice and atmosphere. EXOS-D and MOS-1 satellite observation and the experiments on penguin foraging ecology were also important programs. All these scientific experiments were performed successfully. The particular success of the field experiments of ACR was partly due to the better sea ice condition that guaranteed safe activities on sea ice throughout the year. Regarding the maintenance of the station, a new program on the waste disposal has started in relation to the conservation of the Antarctic environment. A large amount of the disposed waste was brought back to the country. departmental bulletin paper